DETERMINAN DISPARITAS ANTAR WILAYAH DI INDONESIA - Rosmeli, Rosmeli (Jurnal Paradigma Ekonomika, 2011)
In the New Order era, the Indonesian government has made a paradigm of development as the foundation is the reference value of all government policies, it is this which causes the system of centralized government. So there is inequality of development between regions. Based on the background above, this study aimed to find out the impact of fiscal decentralization on diparitas among regions in Indonesia and know the factor-factor disaparitas zoom in and between regions in Indonesia. The data used are secondary data with 19-year time series. Since the implementation of research results show an impact of fiscal decentralization on the growing disparities between regions in Indonesia when compared with the prior fiscal decentralization. Allocation of funds for the Health Sector, Capital Investment in State and central government transfers to the regions enlarging disparities between regions in Indonesia, while the allocation of funds for education and road infrastructure to reduce Inter-Regional Disparity in Indonesia. Keywords: Decentralization and Inequality